East Timor : Policy Challenges for a New Nation - World Bank (Washington, DC, 2013)
The main challenge facing East Timor, is how to reconcile a simultaneous existence of acute poverty and severe shortage of human management skills, with solid prospects of future flows from the country's natural resource wealth. Policies to meet these two priorities - sustained poverty and sound management of natural resources - are the focus of this report. It looks at the pressing concerns of managing the economic transition from the United Nationals Transitional Administration in East Timor (UNTAET) within the next two years; at the issue of wealth creation and the need to enhance the private investment climate; at the need to devise a framework for saving the oil and gas revenues; at the importance of raising human development standards; at the limited number of qualified personnel able to formulate high priority development objectives, compounded by the need to build effective governance; and, at the overwhelming incidence of poverty in rural areas, and the strong correlation between consumption poverty, and low levels of education. In setting a strategy for growth and poverty reduction, the report highlights the importance of maintaining the prevailing efforts at raising farm incomes, and productivity, while improving the quality of rural education, and health facilities, including a tax policy vision that can play a role to avoid exacerbating urban bias. On improving the business environment, there is need for capacity building, and micro-finance programs, but within an adequate legal framework, and prudential regulations. The administrative priorities would require enhanced citizen monitoring on government performance, with an input in public services to improve transparency - which would emerge from an assessment of cost, effectiveness, and capacity.